Facticidad y acción de tutela: presentación preliminar de un estudio empírico de la formulación y efectos de la acción de tutela en el marco colombiano, entre los años 1992-2011. (2014)
This text corresponds to the partial results of the research “Facts and Protection Action”; it develops an interest in the realization of constitutional norms through the filing and enforcement of the tutela actions in the Colombian context, between 1992 and 2011.Thus, it brings a first investigative guidance related to the construction of the concept of an unconstitutional state of affairs, in the doctrine of the Colombian Constitutional Court, as a tool of judicial activity to protect the factual implementation of the 1991 Political Constitution. In this sense, using the census method for the collection and selection of jurisprudence an initial analysis is made of the constitutional doctrine on the proposed category